2014
DOI: 10.1021/es502739m
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Acidification Increases Copper Toxicity to the Early Life History Stages of the Polychaete Arenicola marina in Artificial Seawater

Abstract: The speciation and therefore bioavailability of the common pollutant copper is predicted to increase within the pH range anticipated under near-future ocean acidification (OA), hence the potential exists for copper toxicity to marine organisms to also increase. We investigated the impact of OA (seawater pH values of 7.77 (pCO2 1400 μatm) and 7.47 (pCO2 3000 μatm)) upon copper toxicity responses in early life history stages of the polychaete Arenicola marina and found both synergistic and additive toxicity effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 83 publications
1
53
2
5
Order By: Relevance
“…Another study carried out with larvae of Arenicola marina submitted at different pH levels (8.28, 7.77, 7.47) also reported that pH decrease negatively affected the fertilization success. The same authors also stated that larval survival was reduced when exposed to pH 7.77 during 5 days (Campbell et al, 2014). Concerning to the temperature results, from the present work it is possible to conclude that the regenerative ability increases significantly with the increase of temperature, both in terms of number of days needed to achieve full regeneration as in the number of chaetigers regenerated, regenerating faster and more chaetigers with the increase of temperature.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Another study carried out with larvae of Arenicola marina submitted at different pH levels (8.28, 7.77, 7.47) also reported that pH decrease negatively affected the fertilization success. The same authors also stated that larval survival was reduced when exposed to pH 7.77 during 5 days (Campbell et al, 2014). Concerning to the temperature results, from the present work it is possible to conclude that the regenerative ability increases significantly with the increase of temperature, both in terms of number of days needed to achieve full regeneration as in the number of chaetigers regenerated, regenerating faster and more chaetigers with the increase of temperature.…”
Section: Discussionsupporting
confidence: 73%
“…As a result of human activity, the atmospheric CO 2 concentrations increased from 280 ppmv in 1750 (pre-industrials atmospheric CO 2 levels) to over 391 ppmv in 2011 (IPCC, 2013), corresponding to a reduction of 0.1 units in the oceans pH (Caldeira and Wickett, 2003;IPCC, 2013), and it is expected that pH will further decrease from 0.06 to more than 0.3 units within the end of the 21st century (IPCC, 2013). Several studies revealed that the pH decrease, associated with changes in seawater chemistry, seem to have negative effects on marine ecosystems, namely on bivalves, crustaceans and fish survival capacity, physiology, growth, reproductive capacity, behaviour and development (among others, Campbell et al, 2014;Doney et al, 2012;Dupont and P€ ortner, 2013;Garrard et al, 2013;Lane et al, 2013;Langenbuch and P€ ortner, 2003;Langenbuch et al, 2006;Michaelidis et al, 2005;Widdicombe and Spicer, 2008;Wickens, 1984). Additionally, reproductive capacity may also be affected by water acidification (Widdicombe and Spicer, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have focused on the impact of OA and metals such as cadmium (Cd) and copper (Cu) on marine animals 2426 . OA is expected to modify the bioavailability of metals 27 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the common metal contamination such as copper together with CO 2 exposure might stimulate the adverse effects to organisms, generally supporting a synergistic effect scenario (Campbell et al 2014). In the present study, Manila clams exhibited significant mortality and siphon releasing at pH 6.38 after exposure to a combination of copper (50 μg Cu L −1 ) and CO 2 (p < 0.05) (Fig.…”
Section: Combined Effect Of Co 2 and Copper On Manila Clamsmentioning
confidence: 95%